Immunoendocrine responses over a three week international Rugby Union series - Cunniffe, B.; Hore, A. J.; Whitcombe, D. M.; Jones, K. P.; Davies, B.; Baker, J. S. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study evaluated changes in immunoendocrine makers over an international series in professional rugby union players (N.=8). METHODS: Venous bloods were taken on camp-entry, as well as before and after (0, 14 and 38 h) two games spaced over 21-days. Samples were analysed for changes in serum C-reactive protein (CRP), cortisol (C), testosterone (T), blood leukocytes, interleukin 6 (IL-6) and creatine kinase (CK). RESULTS:Significant reductions in CK activity and CRP concentrations were evident on day 5 (pre-game 1) when compared to camp-entry (day 1); P<0.05. A large acute-phase response was observed following both games. Differences in the magnitude of this response appeared dependant on the number of collisions players experienced during play. Compared to camp-entry, sharp increases in C (40%) and decreases (37%) in T were evident after both games; P<0.05. A gradual increase in T/C ratio was observed throughout the tournament; values 35% and 45% higher on days 19 and 21 than those observed at camp-entry (P<0.05). CONCLUSION: Current data suggests that improved physiological recovery can be achieved during an international rugby union series. Monitoring of previous club activity is essential to ensure optimal player readiness prior to participation in international rugby union games.